Distributed consensus of heterogeneous switched nonlinear multiagent systems with input quantization and DoS attacks - Guo, Shiyu; Zhao, Xudong; Wang, Huanqing; Xu, Ning (Applied mathematics and computation, 2023)
•Different from the nonlinear MAS in [8] whose all agents are second-order, in this paper, the considered MAS consists of first-order and second-order agents simultaneously. Moreover, all agents are considered to have multiple modes and then exhibit the switching feature. Therefore, the MAS model of this paper is more general.•To cope with the issue of DoS attacks on communication channels of systems, an underlying topology switching mechanism is proposed to ensure tolerance for network disconnections. Meanwhile, the DoS attack frequency and attack time ratio are given to characterize the features of DoS attacks. Furthermore, an efficient consensus algorithm is presented by employing the back-stepping technique and the Lyapunov function method.•In contrast to [38], the hysteretic quantization input is considered for switched nonlinear MASs under DoS attacks in this paper, which attenuates the impact of hysteretic quantizers on control performances. Besides, global information is not used in the protocol design, and the dynamics of agents in this study need not to strictly abide by the nonlinear Lipschitz condition. Hence, the developed control scheme in this paper is distributed. In this paper, the consensus tracking control problem is investigated for a class of heterogeneous switched nonlinear multiagent systems (MASs) with input quantization under denial-of-service (DoS) attacks, where first-order agents and second-order agents exist simultaneously, and each agent shows the switching characteristic. Due to the prevalence of DoS attacks in communication channels, a DoS attack model is constructed in this study, and the upper bounds on the duration and frequency of DoS attacks are given. Meanwhile, taking the chattering phenomena of control inputs into account, a hysteresis quantizer is introduced to overcome the issue of the undesirable input chattering. Hence, a new anti-attack distributed consensus protocol is developed such that MASs with input quantization can effectively resist the impact of DoS attacks. Based on the Lyapunov stability theory, the boundedness of all signals in the closed-loop system is verified and the consensus target can be achieved. Finally, the effectiveness of the proposed control scheme is demonstrated by two simulation examples.